2016
DOI: 10.1044/2015_ajslp-14-0201
|View full text |Cite
|
Sign up to set email alerts
|

Who Receives Speech/Language Services by 5 Years of Age in the United States?

Abstract: Purpose: We sought to identify factors predictive of or associated with receipt of speech/language services during early childhood. We did so by analyzing data from the Early Childhood Longitudinal Study-Birth Cohort (ECLS-B; Andreassen & Fletcher, 2005), a nationally representative data set maintained by the U.S. Department of Education. We addressed two research questions of particular importance to speech-language pathology practice and policy. First, do early vocabulary delays increase children's likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 91 publications
(94 reference statements)
4
46
0
2
Order By: Relevance
“…Targeting interventions should be guided by cumulative risk models based on child and family factors identified as important to prognosis. These factors are considered when children present to specialist services; however, many children with low language do not (Morgan et al., ; Skeat et al., ). The application of cumulative risk models to targeting in communities ‘at risk’ of both language difficulties and limited access to services should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting interventions should be guided by cumulative risk models based on child and family factors identified as important to prognosis. These factors are considered when children present to specialist services; however, many children with low language do not (Morgan et al., ; Skeat et al., ). The application of cumulative risk models to targeting in communities ‘at risk’ of both language difficulties and limited access to services should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Speech therapists can also be consulted for various medical reasons, and access to speech therapists is associated with socioeconomic status. 41 Furthermore, because the study outcomes were limited to three subtypes of neurodevelopmental disorders (pervasive developmental disorders, mental retardation and visits to a speech therapist as a proxy for communication-related disorders), no conclusion can be drawn concerning all of the other subtypes of neurodevelopmental disorders.…”
Section: Open Accessmentioning
confidence: 99%
“…Approximately 8 per cent of children at school entry may have DLD (Norbury et al, 2016), making it as prevalent as childhood obesity (reported to be 7% Australian Bureau of Statistics, 2009) although this figure is likely to be much higher once children with less pronounced difficulties are included (Locke et al, 2002;Law et al, 2011) and when children across from across the social spectrum are compared (McKean et al, 2018). Access to services was an issue not directly addressed by Warnock but it is clear that it is not easy for all children to access the services they need and it is often the families who are most in need of these services who access them the least (Moore et al, 2015) and cost, availability and accessibility may also be issues (Ou et al, 2011;Morgan et al, 2016). A recent Australian study by Reilly and colleagues mapped the distribution of speech pathology services across metropolitan Melbourne and examined the level of need in these areas according to language vulnerability and social disadvantage (Reilly et al, 2016).…”
Section: Education and Healthmentioning
confidence: 99%